PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN MELALUI EMPLOYEE ENGAGEMENT (STUDI PERSEPSIONAL PADA KARYAWAN BALAI BESAR PULP DAN KERTAS BANDUNG) - Sarifatul Amanah, - (2022)
This study aims to determine the description of transformational leadership, employee engagement and employee performance at Balai Besar Pulp and Kertas Bandung and also to determine the effect of transformational leadership on employee performance through employee engagement at Balai Besar Pulp and Kertas Bandung. This study uses a quantitative method with a population and a sample of 82 employees of the Bandung Pulp and Paper Center, using the Nonpropability Sampling with Saturated Sampling. The analytical technique used is descriptive analysis, Pearson product moment and path analysis. Hypothesis testing using t-Test to see the effect partially and F-Test simultaneously. The results of this study indicate that transformational leadership has an indirect effect on employee performance through employee engagement. The type of mediation provided is partial mediation where transformational leadership can still have a direct effect on employee performance even though the level of influence is low, and it changes significantly when the employee engagement included in the analysis.